Enhancing Indonesia’s Education Quality: Identifying and Addressing Key Challenges - Tarigan, Ruth Abigail (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Education is an important effort in improving the quality of human resources. The purpose of this study is toevaluate the weaknesses in Indonesia’s current education system. Education is recognized as a top priority in every country, and the quality of education is an important indicator of a nation’s progress. This research adopts adescriptive qualitative approach and uses literature research as its method. The author collected information fromsources considered valid and relevant. The results of this study show that the quality of education in Indonesia is still low. This is due to a number of educational problems that Indonesia faces, including macro issues such as a complex curriculum, educational inequality, costs, teacher placement and low teacher quality. Key issues also involve monotonous teachingmethods, inadequate facilities and infrastructure, and unsatisfactory student learning outcomes. In the discussion, some solutions are suggested that are expected to overcome the problems of education in Indonesia and improve the quality of education, so that Indonesia can compete with or even surpass other countries.This paper aims to increase individual awareness in building a better and more advanced Indonesia, as well aspreparing quality human resources.